2021
DOI: 10.1029/2020je006803
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Oxalate, Acetate, and Perchlorate Mixtures and the Implications for Organic Salts on Mars

Abstract: Organic salts, such as Fe, Ca, and Mg oxalates and acetates, may be widespread radiolysis and oxidation products of organic matter in Martian surface sediments. Such organic salts are challenging to identify by evolved gas analysis but the ubiquitous CO 2 and CO in pyrolysis data from the Sample Analysis at Mars (SAM) instrument suite on the Curiosity rover indirectly points to their presence. Here, we examined laboratory results from SAM-like analyses of organic salts as pure phases, as trace phases mixed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 90 publications
(250 reference statements)
4
30
0
Order By: Relevance
“…SAM EGA pyrolysis experiments of 13 samples demonstrated that CO 2 evolved below 550 °C had a broad range of δ 13 C (−25 ± 20‰ to +56 ± 11‰) representing multiple carbon sources ( 22 ). In addition to the previously discussed instrument carbon source, carbon could come from oxidation or decarboxylation of Martian organics or exogenous carbon ( 17 , 22 28 ). Recent work ( 28 ) showed that SAM-like pyrolysis of metastable organic salts such as acetates and oxalates produce CO 2 and CO below 550 °C, putting upper limits for abundances of these compounds in SAM pyrolysis experiments as high as 2 to 3 wt%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAM EGA pyrolysis experiments of 13 samples demonstrated that CO 2 evolved below 550 °C had a broad range of δ 13 C (−25 ± 20‰ to +56 ± 11‰) representing multiple carbon sources ( 22 ). In addition to the previously discussed instrument carbon source, carbon could come from oxidation or decarboxylation of Martian organics or exogenous carbon ( 17 , 22 28 ). Recent work ( 28 ) showed that SAM-like pyrolysis of metastable organic salts such as acetates and oxalates produce CO 2 and CO below 550 °C, putting upper limits for abundances of these compounds in SAM pyrolysis experiments as high as 2 to 3 wt%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously discussed instrument carbon source, carbon could come from oxidation or decarboxylation of Martian organics or exogenous carbon ( 17 , 22 28 ). Recent work ( 28 ) showed that SAM-like pyrolysis of metastable organic salts such as acetates and oxalates produce CO 2 and CO below 550 °C, putting upper limits for abundances of these compounds in SAM pyrolysis experiments as high as 2 to 3 wt%. These molecules may be present as radiolytic decomposition products of more complex organics ( 29 , 30 ) or could represent simple molecules formed in situ by photolysis or electrochemistry ( 4 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2017 ; Lewis et al. 2021 ). These indirect measurements of organic molecules and organic salts, along with the direct detections and inferences from laboratory work, suggest that hundreds or even thousands of parts per million (by weight) of organic molecules may have been present in the sediments within Gale crater (Sutter et al.…”
Section: Assessment Of Habitabilitymentioning
confidence: 99%
“…The phyllosilicate nontronite was chosen because evidence of similar phyllosilicates has been observed in several samples (e.g., Bristow et al, 2015Bristow et al, , 2018McAdam et al, 2022;Thorpe et al, 2022). The carbon-bearing species were chosen to represent various oxidation states of carbon that could potentially be found on Mars and affect EGA results, including contamination within SAM (Eigenbrode et al, 2018;Freissinet et al, 2019;Glavin et al, 2013;Lewis et al, 2021).…”
Section: Laboratory Samples and Preparationmentioning
confidence: 99%